Pengaruh Pembiayaan Murabahah Dan Financing To Deposit Ratio Terhadap Profitabilitas Pada BNI Syariah - Pertiwi, Annisa Dharma; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2018)
The purpose this research is to find out the influences of murabahah financing and Financing to Deposit Ratio (FDR) toward the profitability in the case of ROA in BNI Syariah. The research is using secondary data reserved from quarterly finance report of BNI Syariah 2010 – 2017 and it has 31 data. The research analysis techniques using multiple linear regression and hypothesis in the form of T-test, F-test, and R2 test. The result showed that murabahah financing and Financing to Deposit Ratio (FDR) do not influence significantly toward ROA of BNI Syariah neither in the case of partially nor simultanly.